Methods to enhance the dynamic range of digital cameras - Yeo, Wilson Han Xiang (Nanyang Technological University, 2019)
The purpose of this report is to address the problems faced by digital cameras today and to seek possible methods to enhance the dynamic range of digital cameras. High dynamic range (HDR) imaging is one of the major challenges faced by digital cameras today. Although, digital cameras today have seen major improvements in their dynamic range, it is still inevitable that HDR images are required to portray the entire details of a scene that exceeds the dynamic range that of the digital camera. Therefore, this report will investigate and analyze images obtained, in MatLab environment. The analysis involves obtaining a response function of the RGB (Red, Green & Blue) channels between HDR image and non-HDR images. Through this experiment, it is observed that low intensity values ranging from 0 – 25 experienced an exponential increase in its pixel intensity value from a non-HDR to an HDR image. However, this is not true at higher intensity values. As intensity increases from 25 to 255, the rate of change in pixel intensity value is almost at a constant. This response function can then be used to search for possible methods to improve the dynamic range of digital cameras.